Analysis of Risk Factors in The Incident of Myopia in Students at The Al-Fakhry Hadiwijaya Islamic Boarding School Kajen - Wahju Ratna Martiningsih; Chamim Faizin; Swasty Swasty; Dasif Syahrul Muharam (International Journal Of Health Science, 2026)
In Indonesia, refractive errors are the most common eye disorder, affecting approximately 25% of the population or around 55 million individuals. Students in Islamic boarding schools are particularly vulnerable to myopia due to study habits such as reading while lying down, maintaining a reading distance of less than 30 cm, and using inadequate lighting. This study aims to analyze risk factors associated with myopia among students aged 14–18 years at Al-Fakhry Hadiwijaya Islamic Boarding School, Kajen. The research employed a quantitative observational analytic design using a cross-sectional approach. Total sampling was applied in December 2023, involving students from grades VIII MTs to XII MA who had lived in the boarding school for at least one year. Data were collected using questionnaires, Snellen charts, trial frames, lux meters, and visual inspection with correction. Statistical analysis was performed using the chi-square test, and ethical approval was obtained (No: 098/EC/KEPK-FK/UNIMUS/2023). The study involved 41 eligible respondents, showing that 56.1% experienced myopia while 43.9% did not. The most dominant risk factors identified were poor lighting (73.1%), improper reading position (69.2%), and close reading distance (38.1%). Statistical results indicated significant relationships between room lighting (p=0.004), reading position (p=0.026), and reading distance (p=0.017) with myopia occurrence. Among these factors, inadequate indoor lighting showed the strongest association with myopia incidence among students.